2019
DOI: 10.1109/access.2019.2900422
|View full text |Cite
|
Sign up to set email alerts
|

D2D Communication Mode Selection and Resource Optimization Algorithm With Optimal Throughput in 5G Network

Abstract: Aiming at the problem of device-to-device (D2D) communication mode selection and resource optimization under the joint resource allocation mode in the 5G communication network, a probabilistic integrated resource allocation strategy and a quasi-convex optimization algorithm based on channel probability statistical characteristics are proposed. This strategy and algorithm guarantee D2D. Communication maximizes total system throughput while maximizing access. The analysis results show that this algorithm can sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 17 publications
(13 reference statements)
0
29
0
Order By: Relevance
“…By using this information, the BS decides in each scheduling period the communication mode for each transmission, together with the allocated resources. The results achieved in [21] showed that this proposal can significantly improve the system throughput and reduce the interferences between UEs. The results show that the use of dedicated resources for the D2D links is preferred to provide higher UE performance.…”
Section: Related Workmentioning
confidence: 88%
See 2 more Smart Citations
“…By using this information, the BS decides in each scheduling period the communication mode for each transmission, together with the allocated resources. The results achieved in [21] showed that this proposal can significantly improve the system throughput and reduce the interferences between UEs. The results show that the use of dedicated resources for the D2D links is preferred to provide higher UE performance.…”
Section: Related Workmentioning
confidence: 88%
“…It also incorporates constraints to guarantee a certain degree of load balancing among the different BSs of the system. Another example is found in [21]. In this work, two UEs in proximity can communicate using a traditional SH connection, or through a direct D2D connection with dedicated resources or sharing resources with other active cellular transmissions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of works deal with interference management for D2D links [9]- [25], each of which targets a slightly different system model or problem target. For example, the works differ in whether downlink bands [11], [19] or uplink bands [9], [10], [12]- [18], [20]- [25] are considered, in whether fixed transmission powers are assumed [9], [12], [13], [22]- [24] or power control is part of the optimization [10], [11], [14]- [21], [25], whether frequency reuse is constrained to one-fold reuse by D2D links [9]- [11], [14], [18], [20], [25] or multiple D2D links may use the same frequency [12], [13], [15]- [17], [19], [21]- [24], or in the optimization target, which typically is assumed to be the sum-rate [9], [10], [12], [13], [16]- [23], [25] but can also be proportional fair rate [24], a general utility [11] or just the satisfaction of rate constraints [15]. Due to the complexity of the considered problem, various solutions have been proposed, each tailored to a...…”
Section: A Related Work and Contributionmentioning
confidence: 99%
“…Note that more related work exists for multi-fold reuse without power control [12], [13], [22], [23] and one-fold reuse with power control [10], [11], [14], [18]- [20], [25]. However, fixed powers yield a completely different, simpler problem that is purely combinatorial.…”
Section: A Related Work and Contributionmentioning
confidence: 99%